2013
DOI: 10.1186/1471-230x-13-141
|View full text |Cite
|
Sign up to set email alerts
|

MYC, FBXW7 and TP53 copy number variation and expression in Gastric Cancer

Abstract: BackgroundMYC deregulation is a common event in gastric carcinogenesis, usually as a consequence of gene amplification, chromosomal translocations, or posttranslational mechanisms. FBXW7 is a p53-controlled tumor-suppressor that plays a role in the regulation of cell cycle exit and reentry via MYC degradation.MethodsWe evaluated MYC, FBXW7, and TP53 copy number, mRNA levels, and protein expression in gastric cancer and paired non-neoplastic specimens from 33 patients and also in gastric adenocarcinoma cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…Pervious literatures revealed FBXW7 functions in other cancers. FBXW7 expression downregulation induced liver, stomach and breast cancer tumorigenesis [13][14][15]. Our study result coordinates with previous research, FBXW7 is an important tumor suppressor gene, and little is known about FBXW7 tumor suppression mechanism.…”
Section: Resultssupporting
confidence: 86%
“…Pervious literatures revealed FBXW7 functions in other cancers. FBXW7 expression downregulation induced liver, stomach and breast cancer tumorigenesis [13][14][15]. Our study result coordinates with previous research, FBXW7 is an important tumor suppressor gene, and little is known about FBXW7 tumor suppression mechanism.…”
Section: Resultssupporting
confidence: 86%
“…VIC/TAMRA-labeled TaqManCopy Number Reference Assay RNAse P (#4403326; Life Technologies, Foster City, CA, United States) was used as an internal control. All the real-time qPCR reactions were performed in quadruplicate with gDNA using a 7500 Fast Real-Time PCR system (Life Technologies, Foster City, CA, United States) as described previously[13]. The copy number of each sample was estimated by CNV analysis using Copy Caller Software V1.0 (Life Technologies, Foster City, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that Myc and Max proteins in exosomes derived from gastric cancer cells downregulated the expression and promoter binding activity of NKX6.3, which is a transcription factor for GKN1 . The amplification and overexpression of Myc are frequently detected in gastric cancers . Importantly, the expression of Myc was higher in advanced GC than in early stage GC and in metastasis .…”
Section: Discussionmentioning
confidence: 92%